(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Fungi effectively eliminate heavy metals from wastewater through the processes of bioaccumulation and biosorption. Fungi were isolated from contaminated locations to enhance their capacity to endure and eliminate heavy metals from wastewater. Bacterial and fungal samples were extracted from Hisar, Haryana using an enrichment culture. We conducted experiments on fungal isolates that exhibited resistance to heavy metals (Pb, Cd, Cr, and As) at concentrations of up to 100 ppm. The objective was to determine their ability to eliminate these metals from liquid media containing 50 ppm of each metal. This study investigated the species Aspergillus nidulans, Rhizopus arrhizus, and Trichoderma hamatum. Aspegillus nidulans and Rhizopus arrhizus could absorb 31.04mg/g and 26.55mg/g of Lead, respectively. A. nidulans and R. arrhizus shown high efficiency in removing Cd from polluted samples, with uptake capacities of 25.01 mg/g and 23.71 mg/g, respectively. Trichoderma hamatum efficiently absorbed Cr (13.21mg/g) and As (7.17mg/g). The molecular sequencing analysis identified three distinct strains: Aspergillus nidulans strain PSGSS08, Trichoderma hamatum strain FBL587, and Rhizopus arrhizus strain FBL578. These fungi can effectively eliminate elevated levels of metals from wastewater and industrial effluents, making them a highly attractive option for biosorption.